40 Jahre Bundesverband Bildender Künstler in Kassel und Nordhessen. (Kassel : BBK (Bundesverband Bildender Künstler), 1988)
Bunge, Kurt ; Burek, Vincent ; Delsing, Bernard ; Deventer, Friedel ; Döbel, Carl ; Frank, Franz ; Gerstgrasser, Siegfried ; Günther, K.F. ; Halter, Gerd ; von der Heid, Peter ; Jaekel, Hildegard ; Kausch, Werner ; Kneisel, Wilhelm ; Leder, Mic ; Meier-Schomburg, Klaus ; Nebel, Kay Heinrich ; etc.
boek